Dynamic Monitoring and Displaying Noise Levels in Populated Areas - Marija Kovačević; Dario Pović; Tomislav Keser; Dalibor Mesarić (International Journal of Electrical and Computer Engineering Systems, 2013)
Noise is every unwanted sound that surrounds us. Noise has many sources and lately it has become a large-scale problem. Traffic is one of the most important causes of noise. According to its impact on human health, there are regulations that designate maximum permissible noise levels in areas where people work and live. Related work mainly refers to theoretical knowledge applied in numerous scientific papers. There are many states and cities such as Finland, Mexico City, etc., where noise control is recognized as an important issue. Since there are no similar projects in Croatia, we have decided to tackle the problem of noise control. In this paper, we have presented the basic idea of a noise measurement device. Furthermore, we have shown the principle of networking devices in the sensory network. Finally, we have described and exemplified the method for displaying the measured data using the QGIS programming tools. The final idea is to create a system that will collect data and display them in almost real time through a web interface.